End‐stage renal disease and severe aortic stenosis: Does valve replacement improve one‐year outcomes?. Issue 6 (17th February 2017) - Condado, Jose F.; Maini, Aneel; Leshnower, Bradley; Thourani, Vinod; Forcillo, Jessica; Devireddy, Chandan; Mavromatis, Kreton; Sarin, Eric L.; Stewart, James; Guyton, Robert; Simone, Amy; Keegan, Patricia; et al.
Abstract : Background: Treatment for patients with end‐stage renal disease (ESRD) and severe aortic stenosis (AS) includes balloon aortic valvuloplasty (BAV), surgical (SAVR), or transcatheter (TAVR) aortic valve replacement. We compared outcomes among these strategies. Methods: A retrospective review of patients with ESRD undergoing treatment for severe AS between 07/2007 and 06/2015 was performed at our center. Patients were classified based on treatment: BAV‐only, TAVR, or SAVR. Baseline characteristics and 30‐day outcomes were compared among groups. A 1‐year survival analysis was performed. Results: Of 85 patients, 25 (29.4%) underwent BAV, 30 (35.3%) TAVR, and 30 (35.3%) SAVR. Patients in the SAVR group, compared to the BAV or TAVR patients, were younger (63 vs. 74 vs. 71 years, P = 0.02) and had less prior stroke (3.3% vs. 12.0% vs. 30.0%, P = 0.008). While all BAV patients had NYHA class III/IV, 93.3% and 76.7% of patients had NYHA class III/IV in the TAVR and SAVR group, respectively ( P = 0.001). BAV patients were less likely to have atrial fibrillation than TAVR or SAVR patients (16.0% vs. 43.3% vs. 50.0%, P = 0.03). All patients were high risk, but there was a statistical trend to lower STS scores in the SAVR group (8.6% vs. 13.5% vs. 13.5%, P = 0.08). There was no significant difference in 30‐day mortality (16.7% vs. 10.0% vs. 10.0%, P = 0.74), but BAV treated patients had an increased 1‐year mortality compared to those treated with TAVR or SAVR (87.0% vs. 32.0%, vs. 36.7%, P =<0.001). Independent predictors of 1‐year mortality were a higher STS score (HR 1.026, 95%CI 1.002–1.051) and BAV‐only strategy (BAV vs. TAVR: HR 3.961, 95%CI 1.595–9.840), but dialysis duration and type, and SAVR versus TAVR were not. Conclusions: Patients with ESRD and severe AS have a similar and higher survival with TAVR or SAVR when compared to BAV at 1‐year. These results may influence patient care decisions favoring valve replacement in AS patients with ESRD. © 2016 Wiley Periodicals, Inc.